Trends and socioeconomic disparities in all-cause mortality among adults with diagnosed diabetes by race/ethnicity: a population-based cohort study - USA, 1997–2015. Issue 5 (4th May 2021) - Mercado, Carla; Beckles, Gloria; Cheng, Yiling; Bullard, Kai McKeever; Saydah, Sharon; Gregg, Edward; Imperatore, Giuseppina
Abstract : Objectives: By race/ethnicity and socioeconomic position (SEP), to estimate and examine changes over time in (1) mortality rate, (2) mortality disparities and (3) excess mortality risk attributed to diagnosed diabetes (DM). Design: Population-based cohort study using National Health Interview Survey data linked to mortality status from the National Death Index from survey year up to 31 December 2015 with 5 years person-time. Participants: US adults aged ≥25 years with (31 586) and without (332 451) DM. Primary outcome: Age-adjusted all-cause mortality rate for US adults with DM in each subgroup of SEP (education attainment and income-to-poverty ratio (IPR)) and time (1997–2001, 2002–2006 and 2007–2011). Results: Among adults with DM, mortality rates fell from 23.5/1000 person-years (p-y) in 1997–2001 to 18.1/1000 p-y in 2007–2011 with changes of −5.2/1000 p-y for non-Hispanic whites; −5.2/1000 p-y for non-Hispanic blacks; and −5.4/1000 p-y for Hispanics. Rates significantly declined within SEP groups, measured as education attainment (<high school=−5.7/1000 p-y; high school graduate=−4.2/1000 p-y; and >high school=−4.8/1000 p-y) and IPR group (poor=−7.9/1000 p-y; middle income=−4.7/1000 p-y; and high income=−6.2/1000 p-y; but not for near poor). For adults with DM, statistically significant all-cause mortality disparity showed greater mortality rates for the lowest than the highest SEP level (education attainment and IPR) in each time period. However, patterns in mortality trends and disparity varied by race/ethnicity. The excess mortality risk attributed to DM significantly decreased from 1997–2001 to 2007–2011, within SEP levels, and among Hispanics and non-Hispanic whites; but no statistically significant changes among non-Hispanic blacks. Conclusions: There were substantial improvements in all-cause mortality among US adults. However, we observed SEP disparities in mortality across race/ethnic groups or for adults with and without DM despite targeted efforts to improve access and quality of care among disproportionately affected populations.